Antihyperlipidemic and hepatoprotective activity of extracts of Zingiber cassumunar rhizome, Aguazuma ulmifolia leaves, and their combination in high-fat diet-fed rats - Mahfudh, Nurkhasanah; Sulistyani, Nanik; Kumalasari, Ika D.; Hilal, Ananda K.; Refliandi, Refliandi; Othman, Fezah; Zakaria, Zainul A. (Poznań University of Life Sciences, 2024)
Oxidative stress is related to several metabolic diseases, including hyperlipidemia. Previous studies have shown the antioxidant properties of Zingiber cassumunar rhizomes and Guazuma ulmifolia leaves. The objective of this study was to see how Z. cassumunar rhizomes, G. ulmifolia leaves extracts, and their combinations affect antihyperlipidemic and hepatoprotective activity in a high-fat diet-fed (HFD) rat. The water extract of Z. cassumunar rhizomes and G. ulmifolia leaves was evaporated in a freeze dryer to produce dry extracts. The Wistar rats were assigned into six groups at random: normal, positive, negative, Z. cassumunar rhizome extract at 400 mg/kg BW (ZC), G. ulmifolia leaf extract at 50 mg/kg BW (GU), and the combination of Z. cassumunar rhizome extract and G. ulmifolia leaf extract at (350+50) mg/kg BW (ZC+GU). The rats were fed HFD for 28 days, and the treatment groups also received the extracts for the last 14 days. The study revealed that ZC, GU, and ZC+GU significantly (p < 0.05) reduced the levels of cholesterol and triglyceride when compared to the negative control. These treatments also showed a hepatoprotective effect by reducing the serum glutamic pyruvate transaminase (SGPT) and histopathological observation. The conclusion of the study showed that ZC, GU, and ZC+GU play an essential role in their antihyperlipidemic and hepatoprotective activities.